Mustahik Economic Transformation Through The Distribution Of Productive Zakat Funds And Business Assistance Programs At Baitul Mal Aceh - Damanhur; Mukhlis Muhammad Nur; T. Saifullah; Doli (Jurnal Ekonomi Syariah, Akuntansi dan Perbankan (JESKaPe), 2026)
Poverty remains one of the major economic challenges in Indonesia, including in Lhokseumawe City. In Islamic economics, productive zakat serves as an instrument of economic empowerment that can improve the welfare of mustahik through business capital assistance. This study aims to analyze the economic transformation of mustahik through the distribution of productive zakat funds and business mentoring programs implemented by Baitul Mal Kota Lhokseumawe. The study employed a mixed methods approach with a sequential explanatory design. The quantitative phase involved 86 mustahik selected through purposive sampling and analyzed using descriptive statistics and the Wilcoxon Signed Rank Test to examine differences in income before and after receiving productive zakat assistance. The qualitative phase was conducted through in-depth interviews with Baitul Mal officials to explore the implementation of business mentoring programs and the factors affecting mustahik empowerment. The findings reveal that productive zakat significantly increases mustahik income, as indicated by an Asymp. Sig. (2-tailed) value of 0.000 < 0.05. Most respondents experienced improved income and stronger economic capacity after receiving business capital assistance. However, business mentoring programs have not been optimally implemented due to limitations in institutional capacity, human resources, and budget allocation. To address these challenges, Baitul Mal Kota Lhokseumawe has initiated the MEMPHIS Program in collaboration with Islamic Relief to strengthen sustainable economic empowerment through mentoring, financial management training, and business monitoring. This study concludes that productive zakat contributes positively to the economic transformation of mustahik and will achieve greater effectiveness when supported by continuous business mentoring programs.